2018
DOI: 10.3892/mmr.2018.8960
|View full text |Cite
|
Sign up to set email alerts
|

High glucose upregulates myosin light chain kinase to induce microfilament cytoskeleton rearrangement in hippocampal neurons

Abstract: Chronic hyperglycemia leads to myosin light chain kinase (MLCK) upregulation and induces neuronal damage. However, the underlying molecular mechanism of neuronal damage in hyperglycemia has not yet been fully elucidated. In the present study, hippocampal neuronal cells were cultured and treated with a high glucose concentration (45 mmol/l). The results demonstrated that high glucose induced shrinking of the synapses, nuclear shape irregularity and microfilament damage. Filamentous actin (F-actin) filaments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…ERK1/2 has been shown to phosphorylate myosin light chain kinase (MLCK), which phosphorylates myosin light chain (MLC) at Thr18/Ser19 and thereby stimulates MLC activity [37,38]. Activated MLC promoted microfilament contraction and accelerates cell migration [39]. In this study, FAK and ERK1/2 activated LIPUS enhanced MLC activation, thereby facilitating cell migration, and that this process was inhibited by specific FAK inhibitor (PF-773228) and ERK inhibitor (U0126), the amounts of phospho-FAK, phospho-ERK1/2, phospho-MLC significantly decreased, which was highly possible that LIPUS promotes the BMSCs migration via the phosphorylation and activation of FAK-ERK signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 has been shown to phosphorylate myosin light chain kinase (MLCK), which phosphorylates myosin light chain (MLC) at Thr18/Ser19 and thereby stimulates MLC activity [37,38]. Activated MLC promoted microfilament contraction and accelerates cell migration [39]. In this study, FAK and ERK1/2 activated LIPUS enhanced MLC activation, thereby facilitating cell migration, and that this process was inhibited by specific FAK inhibitor (PF-773228) and ERK inhibitor (U0126), the amounts of phospho-FAK, phospho-ERK1/2, phospho-MLC significantly decreased, which was highly possible that LIPUS promotes the BMSCs migration via the phosphorylation and activation of FAK-ERK signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Green tea protects against hippocampal neuronal apoptosis via the JNK/MLCK pathway. The JNK signaling pathway serves an important role in apoptosis and our previous study found that MLCK serves a role in hippocampal neuronal apoptosis in DE (14). Therefore, the present study further examined the relationship between the JNK pathway and MLCK.…”
Section: Green Tea Improves Cognitive Dysfunction In Diabetic Rats By Inhibiting Hippocampal Neuronal Apoptosismentioning
confidence: 84%
“…Hippocampal neuronal cell culture and identification. The primary hippocampal neurons were cultured according to a previously published method (14). Newborn SD rat were sacrificed by cervical dislocation and the mortality of the animals confirmed by cessation of heartbeat.…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Li Marc Kirschner and Tim Mitchison suggested in (1986s) that, the microtubules can employ its dynamic characteristics of growth and contraction at their plus ends to probe the 3-D space of the cell. In contrary to regular dynamism microtubules, that has a half-life of 5-10 minutes [11][12][13][14][15]. Electrostatics of nanosystems is considered as one of the applications of the microtubules.…”
Section: Introductionmentioning
confidence: 99%